TITLE: EFFECTIVE STRATEGIES FOR TEACHING ENGLISH IN PRESCHOOL EDUCATION - Shamsuddinova Diyoraxon Yorqinbek qizi; Mirzaazizova Farangiz (TADQIQOTLAR, 2025)
Abstract Early  childhood  is  a  critical  period  for  language  development.  Integrating English language instruction into preschool education can greatly influence children’s cognitive and linguistic  growth. This paper explores practical and developmentally appropriate  strategies  for  teaching  English  to  preschool  learners. It  emphasizes the importance of play-based and child-centered methods, the use of authentic materials, and  the  role  of  the  teacher  in  creating  an  immersive  language  environment. Furthermore, the paper underlines the necessity of aligning language instruction with children’s  psychological  and  emotional  development.  Effective  preschool  English education not only lays the foundation for future academic success but also nurtures curiosity and positive attitudes towards language learning.